TLR10 Senses HIV-1 Proteins and Significantly Enhances HIV-1 Infection - Henrick, Bethany M.; Yao, Xiao-Dan; Zahoor, Muhammad Atif; Abimiku, Alash'le; Osawe, Sophia; Rosenthal, Kenneth L. (Frontiers in Immunology, 2019)
Toll-like receptors (TLRs) play a crucial role in innate immunity and provide a first line of host defense against invading pathogens. Of the identified human TLRs, TLR10 remains an orphan receptor whose ligands and functions are poorly understood. In the present study, we sought to evaluate the level of TLR10 expression in breast milk (BM) and explore its potential function in the context of HIV-1 infection. We evaluated HIV-1-infected (Nigerian: n = 40) and uninfected (Nigerian: n = 27; Canadian: n = 15) BM samples for TLR expression (i.e., TLR10, TLR2, and TLR1) using quantitative RT-PCR. The function of TLR10 in breast milk in HIV-1 infected individuals was explored using siRNA knock-down, flow cytometry, ELISA, confocal microscopy, and Western blotting. Here, we report that HIV-1-infected breast milk (BM) from Nigerian women showed significantly higher levels of TLR10, TLR1, and TLR2 expression. Moreover, the level of TLR10 expression in HIV-infected BM was upregulated by over 100-fold compared to that from uninfected control women. In vitro studies demonstrated that TLR10 overexpression contributes to higher HIV-1 infection and proviral DNA integration. Conversely, TLR10 inhibition significantly decreased HIV-1 infection. Notably, HIV-1 gp41 was recognized as a TLR10 ligand, leading to the induction of IL-8 and NF-B activation. The identification of a TLR10 ligand and its involvement in HIV-1 infection enhances our current understanding of HIV-1 replication and may assist in the development improved therapeutic strategies.